Epidemiology of turbot bacterial diseases in China between October 2016 and December 2019 - Gao, Ye; Wang, Qiyao; Liu, Yaokuan; Ma, Yue; Jin, Huaiyuan; Liu, Jingjing; Wang, Huilin; Yan, Yongwei; Li, Jie (Frontiers in Marine Science, 2023)
Turbot (Scophthalmus maximus) is an important commercial fish in China that can be infected by a series of bacterial pathogens, leading to great economic losses. In this study we focused on the epidemiology of turbot bacterial diseases in the major farming areas in China for three years. A total of 155 cases with 446 diseased turbots were investigated, and dominant bacterial pathogens were isolated from 137 cases (344 turbots). Thus, bacteria are the major threat to farming turbot in China. Edwardsiella piscicida was the major pathogen, which isolated as the dominant colony in 62 cases (40.00%) with 151 turbots (33.85%). Aeromonas salmonicida was isolated in 57 cases (36.77%) with 116 turbots (26.01%). Vibrio anguillarum was isolated in nine cases (5.81%), and Streptococcus parauberis in five cases (3.23%). Photobacterium damselae and Mycobacterium marinum were also isolated from one or two diseased fish. Other Vibrio spp. were isolated in 15 cases (9.68%). Two species of pathogen were isolated in 13 cases, and three species (E. piscicida, A. salmonicida, and S. parauberis) in one case. In 19 cases, no bacteria were isolated. Based on the annual disease analysis, we found that the E. piscicida infection proportion of total cases was greatly decreased, which may be caused by the attenuated vaccine inoculated in 2018. The antibiotic resistance of E. piscicida strains isolated in Weifang city was also determined. We found that the resistance to ceftriaxone, doxycycline, and SMZ/TMP were significantly increased from October 2016 to June 2018, and all the E. piscicida isolates exhibited resistance to SMZ/TMP in June 2018. These results indicated that E. piscicida is the major threat to turbot farming in China, and the attenuated E. piscicida vaccine exhibits effective protection. The usage of antibiotics may induce resistance quickly. Thus, development of vaccines is an important work for sustainable development of turbot farming in the future.